1990
DOI: 10.1007/bf00047062
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model for roughness induced crack closure

Abstract: A theoretical model for the effects of grain size on the magnitude of roughness induced crack closure (RICC) at fatigue crack growth threshold has been proposed. With the basic configuration of a crack propagating incrementally along planar slip bands and deflecting at grain boundaries, an idealized zig-zag crack path is considered. The effective slip band length is considered to be equal to grain size. It is assumed that the dislocations emitted from the crack tip upon loading to form the pile-up are complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…This is because of the fact that the FCG test data from regular CT and side-grooved CT specimens agreed als. [11,12,30] In this study, the relatively high fracture-surface roughness observed in the -aged microstructure suggests well with each other. that the dislocation pileup lengths were on the order of the prior-␤ grain size, with the crack deflecting at the prior-␤ E. Fatigue Fracture Mechanisms in the Neargrain boundaries, during crack growth.…”
Section: Effect Of Microstructure On Fcg Behaviorsupporting
confidence: 65%
See 1 more Smart Citation
“…This is because of the fact that the FCG test data from regular CT and side-grooved CT specimens agreed als. [11,12,30] In this study, the relatively high fracture-surface roughness observed in the -aged microstructure suggests well with each other. that the dislocation pileup lengths were on the order of the prior-␤ grain size, with the crack deflecting at the prior-␤ E. Fatigue Fracture Mechanisms in the Neargrain boundaries, during crack growth.…”
Section: Effect Of Microstructure On Fcg Behaviorsupporting
confidence: 65%
“…In any case, this FCG region, crack propagation is accomplished by dislocation movement by mode II shear at the crack tip. Generally, effect could not be attributed to the macroscopic crackplane deviations observed in the FCG tests of the -aged a single slip system is suggested to be active, [11,12,30] promoting a zigzagged crack path in polycrystalline materimicrostructure. This is because of the fact that the FCG test data from regular CT and side-grooved CT specimens agreed als.…”
Section: Effect Of Microstructure On Fcg Behaviormentioning
confidence: 82%
“…The predictions offered by the above expression are in good agreement[ 1] with the experimental results on titanium alloys, nickel base alloys and iron base klloys. In (1), K d is also a direct function of % apart from grain size While analyzing grain size effects on K d, the effect of d also has to be…”
supporting
confidence: 76%
“…
Recently a theoretical model for roughness induced crack closure during threshold fatigue crack growth in metallic systems has been developed [1]. The model closely predicts the functional dependence of crack closure stress intensity level, K d at threshold on grain size.
…”
mentioning
confidence: 99%
See 1 more Smart Citation